Brightling - Lisle, Rebecca (Hot Key Books London, 2014)
Thrown out of the Knip and Pynch Home for Waifs and Strays, Sparrow is an orphan accompanied only by her loyal cat Scaramouch and a single clue to her real family. Sparrow travels to the town of Stollenback where, lost and afraid, she is taken in by Gloriana, a strange and colourful street girl